Phragmotheca centinelensis (Malvaceae, Malvoideae or Matisioideae), a newly-discovered, critically-endangered canopy tree species from a cloud forest in Pacific Ecuador - Juan Ernesto Guevara-Andino; Dawson M. White; Nigel C. A. Pitman; Juan-Carlos Cerón; Andrea Fernández; Daniel Navas-Muñoz; William S. Alverson (PhytoKeys)
During floristic inventories in remnant cloud forests of the Centinela Ridge of the Chocó Region of Ecuador, where less than 7 km2 of forest patches remain across an area of approximately 500 km2, we recently collected a new species in the genus Phragmotheca Cuatrec. We describe and illustrate this new species and contrast its morphology with known congeneric species. Due to its small range, threatened habitat and active targeting by loggers, this species is assessed as Endangered under IUCN Criterion B1B2ab(I,ii,iii,v).